2019
DOI: 10.1029/2018jc014545
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Precursors Triggering the Kuroshio Intrusion Into the South China Sea Obtained by the Conditional Nonlinear Optimal Perturbation Approach

Abstract: The Kuroshio Intrusion (KI) into the South China Sea (SCS) is a key process that greatly modulates the variability of dominant phenomena in the northern SCS. Using the Regional Ocean Modeling System, the optimal precursor (OPR) triggering the KI is obtained by the Conditional Nonlinear Optimal Perturbation (CNOP) approach. The OPRs exhibit the anticyclonic eddies (AEs) spatial pattern in the southern region (19°N–20.3°N, 119°E–122°E) of the Luzon Strait. The evolution processes of the OPRs indicate that the no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…To investigate the utility of targeted observation in improving the prediction of thermal structures in the shallow YS, the Regional Ocean Modeling System (ROMS) was used to solve the three-dimensional Reynolds-averaged hydrostatic Navier–Stokes equation with the Boussinesq approximation 23 . The ROMS utilizes a nonlinear terrain-following vertical coordinate and has been proven to be suitable for regional ocean modeling by a large number of studies 24 27 . The K-profile parameterization scheme is used to calculate the vertical eddy viscosity and diffusivity 28 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate the utility of targeted observation in improving the prediction of thermal structures in the shallow YS, the Regional Ocean Modeling System (ROMS) was used to solve the three-dimensional Reynolds-averaged hydrostatic Navier–Stokes equation with the Boussinesq approximation 23 . The ROMS utilizes a nonlinear terrain-following vertical coordinate and has been proven to be suitable for regional ocean modeling by a large number of studies 24 27 . The K-profile parameterization scheme is used to calculate the vertical eddy viscosity and diffusivity 28 .…”
Section: Methodsmentioning
confidence: 99%
“…Utilizing the CNOP approach, the optimal initial errors that cause the largest nonlinear forecast uncertainty can be calculated, and their spatial patterns help to locate the sensitive areas. To date, CNOP-identified sensitive areas have been proven to be quite effective in a number of oceanic applications, such as the prediction of the ENSO 33 , upstream Kuroshio transport 27 , Kuroshio intrusion into the SCS 24 , Kuroshio large meander 12 and the ocean state in the SCS western boundary current region 10 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the upstream region, the Kuroshio intrusion into the South China Sea is another important event worth investigating. With the ROMS simulation, Liang et al (2019) found that the CNOPs triggering the Kuroshio intrusion into the South China Sea to be localized in the southern part of the Luzon Strait. Additional observations in this area can achieve more than 40.0% improvement for predicting the intrusion process (Liang, 2019).…”
Section: Applications In Designing Observations For Improving the Kurmentioning
confidence: 99%
“…Using the particle-filtering approach, Kramer et al (2012) provided insight into the optimal observation locations for more effectively predicting the decadal path transitions of the Kuroshio Extension (KE). During the past decade, our group has focused on the optimal observation designs for improved prediction of large-scale variations of the Kuroshio (Wang et al, 2013;Liu et al, 2018;Liang et al, 2019; Zhang et al, 2019). We will introduce the details of these studies in the following section.…”
Section: Critical Role Of Numerical Modeling In Advancing Oceanic Obsmentioning
confidence: 99%